Evaluation of the effect of fertilization on the yield of four promising Creole potato clones (Solanum phureja Jud. Et. Buk) in Mutiscua, Norte de Santander (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2019)
This research was carried out to evaluate the effect of fertilization on four promising clones of potato criolla in the municipality of Mutiscua, the farm where the study was carried out is located at 2750 msnm and an average temperature of 14 ° C, the materials are Selected for the superior performance in previous tests performed in the area, these were clone 2, 5, 9 and as a control the Colombia variety (Clone 1). To determine the fertilization dose, soil analysis was taken into account, based on the results, four doses were used: the first dose recommended by the farmer; the second dose: 50% more than soil analysis; The third dose: from soil analysis and the fourth dose: 25% less than soil analysis; The fertilizer application was applied at the time of sowing and weeding. Key morphological variables such as plant height, number of stems, thickness and leaf area were evaluated when the crop was in full bloom. In terms of yield, the number and weight of the tubers were classified into four categories zero, first, second and riche. It was found that there was no significant difference between the clones evaluated, behaving similar in performance, however the clones that showed the highest performance were clone 5 with (21.76 t / ha) and 9 with 21.59 t / he has. To determine the best fertilizer dose, a cost-benefit analysis was performed that identified dose 4 as the best performing with 207.87%.
Keywords: clones; fertilization; Creole potato; yield; Solanun phureja